Programming By Any Other Name. - Schwartz, Ben (Communications of the ACM, 2016)
A letter to the editor is presented in response to the article "Where Code Comes From: Architectures of Automatic Control from Babbage to Algol" by Thomas Haigh and Mark Priestley in the January 2016 issue.